Regional Demographical and Epidemiological Survey of Some Geriatricpsychiatric Disorders in Ekbatan District of Tehran - Arash Mirab Zadeh; Seyed Kazem Malakooti (University of Social Welfare & Rehabilitation Sciences, 2009)
Objectives: According to growing of aged population in Iran and also high prevalence of psychiatric disorders in this group, assessment of demographical and epidemiological studies of psychiatric disorders in subjects 59 years or older in Ekbatan district of Tehran was the aim ofthis study. Methods & Materials: The subjects were chosen randomly from 1422 subjects 59 years or older, who were lived in Ekbatan district of Tehran. Finally 204 subjects were enrolled and completed the General Health Questionnaire and Geriatric Depression scale. Then 104 subjects were selected randomly and interviewed by Composite InternationalDiagnosis Interview to validate psychiatric disorders. Results: The life time prevalence for all psychiatric disorders in thisstudy was 36.9% and the period prevalence was 18.5%. 25.2% of subjects had only one psychiatric disorder and 6.8% and 2.9% of them had «two» and «three or more psychiatric disorders», respectively. Themost prevalence of psychiatric disorders was Major depressive disorder, Dysthymic disorder, Obsessive Compulsive Disorder and Post-Traumatic Stress Disorder, respectively. Conclusion: The results of this study revealed that some psychiatricdisorders in Iranian geriatric population are common and in some respects, this is non-concordant with other study results. It seems that these results can be helpful for mental health services.